Switchable Conductive MOF-Nanocarbon Composite Coatings as Threshold Sensing Architectures - Freund, Pascal; Senkovska, Irena; Kaskel, Stefan (ACS Applied Materials and Interfaces, 2017)
Switchable metal-organic frameworks (MOFs) showing pronounced and stepwise volume changes as a response toward external stimuli such as partial pressure changes were integrated into electron conductive composites to generate novel threshold sensors with pronounced resistivity changes when approaching a critical partial pressure. Two "gate pressure" MOFs (DUT-8(Ni), DUT = Dresden University of Technology, and ELM-11, ELM = Elastic Layer-structured MOF) and one "breathing" MOF (MIL-53(Al), MIL = Material Institute Lavoisier) are shown to cover a wide range of detectable gas concentrations (20-80%) using this concept. The highest resistance change is observed for composites containing a percolating carbon nanoparticle network (slightly above the percolation threshold concentration). The volume change of the MOF particles disrupts the percolating network, resulting in a colossal resistance change up to 7500%. Repeated threshold detection is particularly feasible using MIL-53(Al) due to its high mechanical and chemical stability, even enabling application of the composite sensor concept in ambient environment for the detection of volatile organic compounds at high concentration levels.
CRIS-Team Scopus Importer:2022-04-14
Keywords: composites; gas sensing; metalorganic frameworks; switchable materials; threshold sensors